STRATEGI PENGUATAN AKSES PEREMPUAN TERHADAP KEADILAN MELALUI LEGAL EMPOWERMENT DALAM RANGKA PENGETASAN KEMISKINAN PEREMPUAN - Rima Vien Permata Hartanto; Siany Indria Liestyasari; Adriana Grahani Firdausy (Program Studi Pendidikan Pancasila dan Kewarganegaraan FKIP Universitas Sebelas Maret, 2018)
Definitions and attributes of poverty has been too much attached to the economic aspects, especially measured by the level of income per capita, whereas the root of poverty is lack of access for poor people to participate in determining their own destiny in the decision making process for the purpose of policy formulation in various fields of life. Poverty should also include a lack of understanding and awareness of the law, mechanisms of assistance and legal assistance and access to the political process in decision making. If the poor are involved, then they will get protection of law. This is where the view on poverty from a legal perspective is becoming increasingly important. Poverty experienced by most women in Indonesia, especially women living in rural areas so that poverty limits the capacity of women to access justice. Poor access to justice is then further leads to further women trapped in poverty. Various studies and reports have revealed various obstacles that women face in accessing justice. The main obstacle is the general lack of awareness and understanding of their legal rights. To overcome these obstacles, one of the strategies to improve women's access to justice is legal empowerment or the empowerment law. In general, legal empowerment or the empowerment law is an effort aimed at strengthening the marginalized people, including in this case is a group of women, in order to improve their control over their lives, by making use of legal resources in the community and development activities related and not solely relying on legal institutions (formal). If women are empowered legally, then they get legal protection.Keywords: Legal Empowerment, Acess to Justice, Poverty, Women.